Thermoelectric generator under identical temperature-difference conditions - Sukhabot Thanadhol; Jiamrittiwong Prayut; Puangngernmak Nutdechatorn (E3S Web of Conferences)
Thermoelectric generator (TEG) can directly convert thermal energy to electrical energy using the Seebeck effect. The voltage output of a TEG is a direct variation to the temperature difference between its hot and cold sides, but the impact of temperature distribution on power output is not fully understood. This study evaluated the effect of TEG power output under identical temperature-difference conditions, focusing on the hot and cold side effects. TEG systems with different heating and cooling source temperatures are operated under identical temperature-differences. The system with a higher temperature gradient at the hot side HTR exhibits better performance than the system with a lower temperature gradient at the hot side LTR. The results show that the power output, voltage output, and current output of both conditions differ by 5.85%, 2.71%, and 3.15%, respectively. This difference is attributed to reduced charge carrier mobility due to temperature gradients between the hot and cold sides. The HTR condition promotable for operating a thermoelectric power generator system, the system is turned on frequently.